Alpha Particles Induce Autophagy in Multiple Myeloma Cells - Gorin, Jean-Baptiste; Gouard, Sébastien; Ménager, Jérémie; Morgenstern, Alfred; Bruchertseifer, Frank; Faivre-Chauvet, Alain; Guilloux, Yannick; Chérel, Michel; Davodeau, François; Gaschet, Joëlle (Frontiers in Medicine, 2015)
Objectives Radiation emitted by the radionuclides in radioimmunotherapy (RIT) approaches induce direct killing of the targeted cells as well as indirect killing through the bystander effect. Our research group is dedicated to the development of α-RIT, i.e., RIT using α-particles especially for the treatment of multiple myeloma (MM). γ-irradiation and β-irradiation have been shown to trigger apoptosis in tumor cells. Cell death mode induced by 213Bi α-irradiation appears more controversial. We therefore decided to investigate the effects of 213Bi on MM cell radiobiology, notably cell death mechanisms as well as tumor cell immunogenicity after irradiation. Methods Murine 5T33 and human LP-1 MM cell lines were used to study the effects of such α-particles. We first examined the effects of 213Bi on proliferation rate, double-strand DNA breaks, cell cycle, and cell death. Then, we investigated autophagy after 213Bi irradiation. Finally, a coculture of dendritic cells (DCs) with irradiated tumor cells or their culture media was performed to test whether it would induce DC activation. Results We showed that 213Bi induces DNA double-strand breaks, cell cycle arrest, and autophagy in both cell lines, but we detected only slight levels of early apoptosis within the 120 h following irradiation in 5T33 and LP-1. Inhibition of autophagy prevented 213Bi-induced inhibition of proliferation in LP-1 suggesting that this mechanism is involved in cell death after irradiation. We then assessed the immunogenicity of irradiated cells and found that irradiated LP-1 can activate DC through the secretion of soluble factor(s); however, no increase in membrane or extracellular expression of danger-associated molecular patterns was observed after irradiation. Conclusion This study demonstrates that 213Bi induces mainly necrosis in MM cells, low levels of apoptosis, and autophagy that might be involved in tumor cell death.